Removal of different-age biofilms using carbon dioxide aerosols - Cha, Minju; Hong, Seongkyeol; Lee, Sang-Youp; Jang, Jaesung (KOREAN SOC BIOTECHNOLOGY & BIOENGINEERING, 2014)
Many techniques to inactivate or remove biofilms in a wide variety of applications have been developed. Most of these techniques have been applied to biofilms at their initial stage of growth, since they are generally difficult to eradicate once established. The removal of established biofilms has received relatively little attention. In this paper, we report the effectiveness of periodic jets of carbon dioxide aerosols (a mixture of solid and gaseous CO2) to remove Escherichia coli (XL1-blue) biofilms of different ages (up to 3 weeks) on silicon surfaces. The biofilms were not immersed in liquids after growth/rinsing and were treated with the CO2 aerosols. The CO2 aerosols were generated by the adiabatic expansion of high-pressure CO2 gas through a nozzle. The surface area of the biofilms was measured from fluorescent images before and after applying the aerosols for 11, 20, and 30 cycles (each cycle: 8 sec), to compute the removal efficiency. The removal efficiencies decreased with increasing growth time and for the 3-week-old biofilms, they ranged from 91.5 to 99.6% within 4 min. This technique was highly effective for removing both fresh and old biofilms, but some of the biofilm debris such as growth media remained. Further, this CO2 aerosol technique was compared with other removal techniques.
Keywords: HYDROPHOBIC SURFACES; BACTERIAL DETACHMENT; ADHESION